PENGARUH PROKRASTINASI DAN LEADERSHIP TRAITS TERHADAP PRODUKTIVITAS KARYAWAN DENGAN KOMUNIKASI ASERTIF SEBAGAI PEMODERASI - Handayani; Harijanto Ratana; Mulio Kantjana (LPPM Universitas Buddhi Dharma, 2025)
This research delves into the interplay of procrastination, leadership traits, and assertive communication, examining their combined influence on employee productivity. Procrastination, the tendency to delay tasks, has been identified as a significant factor affecting productivity. Concurrently, leadership traits, including intelligence, self-confidence, determination, and personal integrity, play a pivotal role in shaping employee behavior and performance. This study posits that assertive communication acts as a moderating variable, influencing the relationship between procrastination, leadership traits, and employee productivity. A quantitative approach is employed, utilizing a research model comprising two independent variables: procrastination and leadership traits. Assertive communication serves as the moderating variable, while employee productivity is the dependent variable. The study's hypotheses are tested using data collected from a sample of 159 employees from various companies, representing a diverse age range. The findings reveal that procrastination negatively influences employee productivity, while positive leadership traits positively impact employee productivity. Furthermore, assertive communication is found to have a moderating effect on the relationship between procrastination, leadership traits, and employee productivity. Employees exhibiting lower procrastination tendencies, coupled with effective assertive communication, demonstrate higher productivity levels. Similarly, positive leadership traits, complemented by assertive communication, contribute to increased employee productivity. In conclusion, this research underscores the importance of addressing procrastination and fostering assertive communication within organizations to enhance employee productivity. The presence of assertive communication, along with positive leadership traits, can mitigate the negative effects of procrastination and promote a more productive work environment.